Pengembangan E-Modul Kalkulus Berbasis SETS Terintegrasi Nilai Keislaman Untuk Mahasiswa Program Studi Tadris Matematika - wahyuni, fina tri (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2022)
The aim of this research is to develop a SETS-based Calculus e-module integrated with Islamic values for students of the Tadris Mathematics study program and to assess its validity and practicality. The research method employed is Research and Development (RD) using a 4-stage development model: defining (Define), planning (Design), developing (Develop), and disseminating (Disseminate). Data for the study was collected using a questionnaire instrument, with the test subjects being second-semester students from the Tadris Mathematics program at the Faculty of Tarbiyah, IAIN Kudus. Data analysis involved testing the validity of expert questionnaires and evaluating the practicality of the product. The results indicated: (1) Define—problem identification revealed that students still struggle to understand the teaching materials, which are in the form of printed books, and the methods applied in online lectures. Additionally, Islamic values are not integrated into the teaching materials. (2) Design—product designs were prepared, resulting in SETS-based Calculus e-modules integrated with Islamic values using the Flip Builder application. (3) Develop—product validation by material experts resulted in a score of 3.52, classified as "Valid." Media expert evaluation scored 3.63, also classified as "Valid." The product was validated by religious experts, achieving a "Valid" rating with a score of 3.43. The limited trial scored 2.97, meeting the "Practical" criteria. (4) Disseminate—at this stage, the product is shared through the Tadris Mathematics IAIN Kudus website.ABSTRAKPenelitian ini bertujuan untuk mengembangkan e-modul Kalkulus berbasis SETS yang diintegrasikan dengan nilai-nilai keislaman untuk mahasiswa program studi Tadris Matematika serta menilai validitas dan kepraktisannya. Metode penelitian yang digunakan adalah Research and Development (RD) dengan menggunakan model pengembangan 4 tahap yaitu pendefinisian (Define), perancangan (Design), pengembangan (Develop), dan penyebaran (Disseminate). Data untuk penelitian ini dikumpulkan dengan menggunakan instrumen kuesioner, dengan subjek uji coba adalah mahasiswa semester dua dari program Tadris Matematika Fakultas Tarbiyah IAIN Kudus. Analisis data dilakukan dengan menguji validitas kuesioner ahli dan mengevaluasi kepraktisan produk. Hasil penelitian menunjukkan: (1) Identifikasi masalah menunjukkan bahwa mahasiswa masih kesulitan dalam memahami bahan ajar, yang berupa buku cetak, dan metode yang diterapkan dalam perkuliahan online. Selain itu, nilai-nilai Islam tidak diintegrasikan ke dalam bahan ajar. (2) Desain produk disusun, menghasilkan e-modul Kalkulus berbasis SETS yang diintegrasikan dengan nilai-nilai keislaman menggunakan aplikasi Flip Builder. (3) Validasi produk oleh ahli materi menghasilkan skor 3,52, tergolong “Valid”. Penilaian ahli media menghasilkan skor 3,63, juga tergolong “Valid”. Produk divalidasi oleh ahli agama, mendapatkan penilaian “Valid” dengan skor 3,43. Uji coba terbatas memperoleh skor 2,97, memenuhi kriteria “Praktis”. (4) Penyebaran (Disseminate) - pada tahap ini, produk disebarluaskan melalui website Tadris Matematika IAIN Kudus.